Relationships Between The Elderly Knowledge and The Use of Traditional Antihypertensive Drugs - Henny Yulianita; Alamanda Puspita; Orin Tri Wulan; Hasina Nabilla Nur (Universitas Padjadjaran, 2020)
The aging process will be experienced by the elderly which is a decrease in the ability of the heart that can trigger the occurrence of hypertension. Treatment using herbs is an alternative treatment to overcome hypertension. Some plants that have antihypertensive activity are celery, cat’s whiskers, bay leaves, and noni. This study aimed to identify whether there was a relationship between knowledge of the elderly and the use of anti-hypertensive traditional drugs. This study was a descriptive correlation research with cross sectional approach. The sample of this study were 37 elderly people in one neighborhood of Hegarmanah Village. The sampling technique used total sampling technique. Data were collected using questionnaire through interview. The questionnaire consisted of 11 questions, namely 1 question about whether or not using traditional antihypertensive medication, 10 questions for knowledge variables, The results showed that nearly 65% of respondents used traditional antihypertensive drugs and 22% of the elderly had good knowledge. The results of chi-square test showed no significant relationship between the knowledge of the elderly and the use of traditional antihypertensive drugs with p value 0.13. The social culture had influence to make personal decision to use of traditional antihipertensive drugs.